"Inline" Axial Reconstructed CT Scans Provide a Significantly Larger Assessment of C2 Pedicle Diameter for Screw Placement Compared With "Standard" Axial Scans: Implications for Surgical Planning. Issue 8 (October 2017) - Vizurraga, David E.; Rhee, John M.; Borden, Timothy C.; Mansour, Ashton S.
Abstract : Study Design: Radiologic analysis. Objective: The objective was to compare C2 pedicle diameter and screw feasibility on reconstructed axial computed tomography (CT) cuts created "Inline" (IL) with the intended pedicle screw tract versus unaltered "Standard" (STD) axial cuts. Background Data: Axial CT cuts through the C2 pedicle are commonly evaluated when planning pedicle screw fixation as medial aberrancies of the vertebral artery can significantly narrow pedicle diameter. STD axial CT cuts provided by radiology departments are typically formatted orthogonal to the long axis of the neck or the vertical plumb, which is often not IL with the axis of the intended C2 pedicle screw tract. Materials and Methods: A total of 89 cervical spine CT scans obtained by a single radiology department over 2 years (35 male, 54 female; mean age 64.9 y) were reviewed. STD axial cuts were not manipulated but were assessed as provided. IL axial cuts were created along the intended C2 pedicle screw tract using free, open-source DICOM viewer software. Inner and outer pedicle diameters were measured on axial cuts most closely approximating the isthmus of the intended tract. Results: On STD cuts, the mean outer and inner pedicle diameters were 5.05±1.45 and 2.01±1.31 mm, respectively. By contrast, IL measurements yielded significantly larger outer and inner diameters: 5.85±1.78 and 2.68±1.47 mm ( P <0.01). IL measurement predicted a higher number of pedicles amenable to insertion of a 3.5 mm screw with safety margins of 1 to 3 mm. Conclusions: Reformatted IL axial cuts through the intended path of C2 pedicle screws provide significantly larger assessments of C2 pedicle diameter than those obtained on STD cuts. IL measurements predict C2 screw insertion feasibility in a substantially higher number of pedicles. As assessment of IL cuts may alter surgical decision-making at no added cost or radiation exposure, we suggest that they be obtained whenever considering C2 pedicle screw placement.